Pengembangan desain blangkon dan kemasan blangkon dengan metode Quality Function Deployment (QFD) - Dian Janari (Teknoin, 2018)
SME have an important role in improving the economy. There are a number of fields that many SME are involved in, one of which is in the clothing sector. The object of this research is Blangkon production in Beji Village, Yogyakarta. According to Blangkon craftsmen in Beji, less attractive of Blangkon design and packaging have influenced the decreasing of sales number. This study aims to determine the technical requirements and improvements needed for both variables employing the QFD (Quality Function Deployment) method and HOQ (House of Quality). The customer requirements are consisted of exclusive materials, model, durability, convenience, size, color, style, price, and packaging including logo, motif, form, and material. The results showed that exclusive materials, model, packaging motif, and packaging form are required to be improved. Meanwhile, durability, convenience, packaging logo, and packaging material must be maintained and innovated continously. The remaining criterias are maintained. There are 3 design concepts proposed which the design concept C is selected. The second HOQ is applied in order to obtain technical requirements requested.